2021
DOI: 10.21037/tlcr-20-960
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative systemic immune-inflammation index predicts survival and recurrence in patients with resected primary pulmonary sarcomatoid carcinoma

Abstract: Background: Pulmonary sarcomatoid carcinoma (PSC) is a rare lung cancer subtype. Studies concerning PSC are limited and controversial; therefore, we analyzed the treatment and outcomes of PSC utilizing a relatively large single-institution database. Methods: From January 2003 to December 2018, 262 consecutive PSC patients treated at our institution were retrospectively reviewed. The clinical characteristics, treatments, and outcomes were analyzed. Results: The median survival time (MST) was 22.0 months, with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…It was reported that high systemic immune inflammation index (SII) value was related to poor prognosis in a variety of cancers. Some studies showed that SII can be used to predict the survival of patients with Intrahepatic Cholangiocarcinoma (ICCA)、pulmonary sarcomatoid carcinoma (PSC)、resectable gastroesophageal adenocarcinomas and anal cancer [12][13][14][15]. The results showed that the overall survival of the high SII group was significantly more worsen than that of the low SII group.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that high systemic immune inflammation index (SII) value was related to poor prognosis in a variety of cancers. Some studies showed that SII can be used to predict the survival of patients with Intrahepatic Cholangiocarcinoma (ICCA)、pulmonary sarcomatoid carcinoma (PSC)、resectable gastroesophageal adenocarcinomas and anal cancer [12][13][14][15]. The results showed that the overall survival of the high SII group was significantly more worsen than that of the low SII group.…”
Section: Introductionmentioning
confidence: 99%
“…Jomrich et al [ 27 ] studied 320 consecutive patients undergoing esophagectomy and found that in patients with gastroesophageal junction adenocarcinoma, a high SII was associated significantly with lower survival in patients undergoing neoadjuvant treatment. Zeng et al [ 28 ] revealed that the SII is an important independent prognostic index for pulmonary sarcomatoid carcinoma. Aziz et al [ 29 ] assessed 590 patients with resectable pancreatic ductal adenocarcinoma (PDAC) retrospectively and identified an SII >900 as an independent predictor of cancer-specific survival and recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no consensus on the standard treatment for PSC 18. Fortunately, there is abundant evidence of the survival benefits for patients with early-stage PSC undergoing surgery 8,19,20. Surgical resection is the preferred treatment for early-stage PSC and is also the basis of comprehensive treatment according to the 2021 National Comprehensive Cancer Network guidelines 5.…”
Section: Discussionmentioning
confidence: 99%